SKIN HYPERPIGMENTATION: MODERN VIEWS ON ETIOLOGY AND PATHOGENESIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A brief literature review of the etiology and pathogenesis of hyperpigmentation is presented based on modern scientific publications. The review focuses on the actively studied mechanisms of melanin synthesis in normal and pathological conditions, the physiology of pigment cells melanocytes, their interaction with other structures of the epidermis and dermis, as well as the mechanisms of regulation of melanogenesis. The main factors influencing the occurrence of hyperpigmentation are also covered.